2014
DOI: 10.1038/jcbfm.2014.100
|View full text |Cite
|
Sign up to set email alerts
|

The Cross-Talk between Canonical and Non-Canonical Wnt-Dependent Pathways Regulates P-Glycoprotein Expression in Human Blood–Brain Barrier Cells

Abstract: In this work, we investigate if and how transducers of the 'canonical' Wnt pathway, i.e., Wnt/glycogen synthase kinase 3 (GSK3)/bcatenin, and transducers of the 'non-canonical' Wnt pathway, i.e., Wnt/RhoA/RhoA kinase (RhoAK), cooperate to control the expression of P-glycoprotein (Pgp) in blood-brain barrier (BBB) cells. By analyzing human primary brain microvascular endothelial cells constitutively activated for RhoA, silenced for RhoA or treated with the RhoAK inhibitor Y27632, we found that RhoAK phosphoryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 39 publications
2
35
0
Order By: Relevance
“…One wonders how ABC transporter function is modulated through interactions with other neurovascular unit elements. Certainly, recent studies implicate both canonical and noncanonical Wnt signaling in the regulation of P-glycoprotein expression (Pinzon-Daza et al, 2014). Such signaling is one component of the neurovascular unit's conversations.…”
Section: Perspectives: Where the Field Is Headedmentioning
confidence: 99%
“…One wonders how ABC transporter function is modulated through interactions with other neurovascular unit elements. Certainly, recent studies implicate both canonical and noncanonical Wnt signaling in the regulation of P-glycoprotein expression (Pinzon-Daza et al, 2014). Such signaling is one component of the neurovascular unit's conversations.…”
Section: Perspectives: Where the Field Is Headedmentioning
confidence: 99%
“…88 The authors found that downregulation of β-catenin led to a decrease in P-gp expression. It was also shown in vitro that the inhibition of β-catenin enhanced delivery of doxorubicin, a P-gp substrate, across a BBB epithelial monolayer against glioblastoma cells.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Consistent with this finding, recent study demonstrated that the expression of P-gp in human BBB cells is controlled by a cross-talk between the Wnt/GSK3 canonical pathway and the Wnt/RhoA/RhoAK non-canonical pathway. Increased activity of Wnt/GSK3 canonical pathway reduced GSK3-mediated phosphorylation and ubiquitination of β-catenin, decreasing its proteasomal degradation, enhances its nuclear translocation, and increases P-gp expression (Pinzon-Daza et al, 2014). Similarly, RhoA activation through non-canonical Wnt3/RhoA/RhoAK pathway reduced the activity of GSK3.…”
Section: Introductionmentioning
confidence: 99%